Impact of Metals on (Star)Dust Chemistry: A Laboratory Astrophysics Approach - Bérard, Rémi; Makasheva, Kremena; Demyk, Karine; Simon, Aude; Nuñez Reyes, Dianailys; Mastrorocco, Fabrizio; Sabbah, Hassan; Joblin, Christine (Frontiers in Astronomy and Space Sciences, 2021)
Laboratory experiments are essential in exploring the mechanisms involved in stardust formation. One key question is how a metal is incorporated into dust for an environment rich in elements involved in stardust formation (C, H, O, Si). To address experimentally this question we have used a radiofrequency cold plasma reactor in which cyclic organosilicon dust formation is observed. Metallic (silver) atoms were injected in the plasma during the dust nucleation phase to study their incorporation in the dust. The experiments show formation of silver nanoparticles (~15 nm) under conditions in which organosilicon dust of size 200 nm or less is grown. The presence of AgSiO bonds, revealed by infrared spectroscopy, suggests the presence of junctions between the metallic nanoparticles and the organosilicon dust. Even after annealing we could not conclude on the formation of silver silicates, emphasizing that most of silver is included in the metallic nanoparticles. The molecular analysis performed by laser mass spectrometry exhibits a complex chemistry leading to a variety of molecules including large hydrocarbons and organometallic species. In order to gain insights into the involved chemical molecular pathways, the reactivity of silver atoms/ions with acetylene was studied in a laser vaporization source. Key organometallic species, AgnC2Hm (n = 1–3; m = 0–2), were identified and their structures and energetic data computed using density functional theory. This allows us to propose that molecular Ag–C seeds promote the formation of Ag clusters but also catalyze hydrocarbon growth. Throughout the article, we show how the developed methodology can be used to characterize the incorporation of metal atoms both in the molecular and dust phases. The presence of silver species in the plasma was motivated by objectives finding their application in other research fields than astrochemistry. Still, the reported methodology is a demonstration laying down the ground for future studies on metals of astrophysical interest, such as iron.